PERBANDINGAN EFEKTIVITAS METODE PERKUATAN JALAN TOL IR WIYOTO WIYONO MENGGUNAKAN FRP, STEEL-PLATE DAN TANPA PERKUATAN - Basri, Ricki Mahendra; -, Sutrisno (Jurnal Mahasiswa Terapan, 2026)
This study analyzes the effectiveness of structural strengthening on a 2 km segment of the Ir. Wiyoto Wiyono Elevated Toll Road (Pluit–Tanjung Priok section), which has experienced performance degradation after more than 36 years of operation. The research compares external strengthening methods for reinforced concrete slabs using Fiber Reinforced Polymer (FRP) and Steel Plate Bonding (SPB) through SAP2000 numerical simulations. The evaluation parameters include support reactions, shear force, bending moment, stress, deflection, and maximum load capacity. The results indicate that FRP can increase support reactions by 71% and shear force by 46%, while reducing deflection by up to 83%. Conversely, the SPB method demonstrated superior performance with a 76% increase in support reactions, a 52% increase in shear force, and a highly significant deflection reduction of 99%.  While both methods are effective in enhancing structural stiffness and controlling deformation, neither provided a substantial increase in maximum load capacity. Therefore, the application of either FRP or SPB is highly recommended for strengthening existing structures to extend service life and improve safety standards without drastically altering the primary load capacity.